Foreign trade liberalization and trade-economic integration in Georgia - Ushangi Samadashvili (Foundations and Trends in Modern Learning, 2025)
This paper presents the essence, genesis and significance of foreign trade liberalization and trade-economic integration. It is argued that, on the one hand, in Georgia, with its small economy, it is impossible to achieve universal and differentiated well-being of society without inclusive economic growth, that is, universal involvement in the economy and targeted, fair distribution of increased income, and on the other hand, economic growth itself is unthinkable with an orientation only to small domestic market demand. That is why it is advisable to supplement Georgia’s domestic demand with foreign demand, based on existing and future free trade agreements, in order to increase the scale of the market and achieve a more complete, broad and bilateral trade and economic integration of Georgia, both with the region, the European Union and the world economy. Proposals and recommendations are also proposed to facilitate such integration